The essential role of the Walker A motifs of SUR1 in K-ATP channel activation by Mg-ADP and diazoxide. - Gribble, F; Tucker, S; Ashcroft, F (1997)
The ATP-sensitive K-channel (K-ATP channel) plays a key role in insulin secretion from pancreatic beta-cells. It is closed by glucose metabolism, which stimulates insulin secretion, and opened by the drug diazoxide, which inhibits insulin release. Metabolic regulation is mediated by changes in ATP and Mg-ADP, which inhibit and potentiate channel activity, respectively. The beta-cell K-ATP channel consists of a pore-forming subunit, Kir6.2, and a regulatory subunit, SUR1. We have mutated (independently or together) two lysine residues in the Walker A (W(A)) motifs of the first (K719A) and second (K1384M) nucleotide-binding domains (NBDs) of SUR1. These mutations are expected to inhibit nucleotide hydrolysis. Our results indicate that the W(A) lysine of NBD1 (but not NBD2) is essential for activation of K-ATP currents by diazoxide. The potentiatory effects of Mg-ADP required the presence of the W(A) lysines in both NBDs. Mutant currents were slightly more sensitive to ATP than wild-type currents. Metabolic inhibition led to activation of wild-type and K1384M currents, but not K719A or K719A/K1384M currents, suggesting that there may be a factor in addition to ATP and ADP which regulates K-ATP channel activity.